Algebraic Thinking Ability of Junior High School Students in Solving Linear Equations Problems - Husnul Khatimah Rusyid; Didi Suryadi; Jarnawi Afgani Dahlan; Tatang Herman (Universitas Syiah Kuala, 2024)
Algebraic thinking ability are important for students to master and use algebraic concepts in various situations. Students with good algebraic thinking ability will find it easier to solve real-world problems and understand more abstract mathematical concepts. This study aims to describe students' algebraic thinking ability on linear equation material. Thus, the type of research used is phenomenology with a qualitative descriptive approach. The participants in this study consisted of 37 students; six students with heterogeneous abilities (high, medium, low) were then selected. The research subjects were determined by purposive sampling based on the pattern of answers representing the phenomenon that occurred. Data were collected using algebraic thinking ability tests and interviews to fulfill the validity of the data. The results showed that: 1) students with high algebraic thinking ability can use all indicators of algebraic thinking well. 2) students with medium algebraic thinking ability have difficulty in the indicators of analytical thinking, modeling, and dynamic thinking. 3) students with low algebraic thinking ability have difficulty in all indicators of algebraic thinking, namely generalization, modeling, abstraction, analytical thinking, dynamic thinking, and organization. So, teacher efforts are needed to provide students with an understanding of algebraic thinking so that students can solve math problems well.